Antarctic animals in the collection of Zoological Museum of the Ivan Franko National University of Lviv - Shydlovskyy, I. V. (Ukrainian Antarctic Journal, 2009)
The article presents a brief history of the formation and analysis of collections of Antarctic species of animals, which are stored in the Zoological Museum of Lviv National Ivan Franko University, and presented more than 300 specimens.